No Clinically Relevant Memory Effects in Perinatal Hyperglycemia and Hypoglycemia: A 40-Year Follow-Up of a Small Cohort - Järvinen, Ilkka; Launes, Jyrki; Lipsanen, Jari; Virta, Maarit; Vanninen, Ritva; Lehto, Eliisa; Schiavone, Nella; Tuulio-Henriksson, Annamari; Hokkanen, Laura (Frontiers in Public Health, 2022)
Maternal diabetes mellitus in pregnancy is associated with impairments in memory functions of the offspring in childhood and adolescence but has not been studied in adulthood. The association of perinatal hypoglycemia with memory has not been studied in adulthood either. The combined sequelae of these two risk factors have not been directly compared. We studied general cognitive ability and memory functions in a prospective follow-up of a cohort born in 1971 to 1974. The sample included participants exposed to prenatal hyperglycemia (n = 24), perinatal hypoglycemia (n = 19), or both (n = 7). It also included controls with no early risks (n = 82). We assessed the participants’ Intelligence quotient (IQ), working memory, and immediate and delayed recall of both verbal and visual material at the age of 40. We did not find significant differences in IQ or the memory tests between the groups. We did identify an interaction (p = 0.03) of the early risk with the type of digit span task: compared to the controls, the participants exposed to perinatal hypoglycemia had a larger difference between the forward digit span, a measure of attention, and the backward digit span, a measure of working memory processing (p = 0.022). The interaction remained significant when birth weight was controlled for (p = 0.026). Thus, in this small cohort, prenatal hyperglycemia, perinatal hypoglycemia, and their combination appeared relatively benign disorders. The association of these conditions with neurocognitive impairments in adulthood remains unconfirmed. The significance of the working memory difference needs to be verified with a larger sample.